Thorns amongst Roses? Lived Experience of Philippine Male College Students Aspiring to Become Professional Elementary Teachers - Cahapay, Michael B (International Journal of Educational Studies, 2021)
There is a noticeable under-representation of the male gender particularly in the field of elementary teacher education. The main aim of this paper is to understand the lived experience of male college students aspiring to become professional elementary teachers. As phenomenological research, it involved six purposively selected male students enrolled in a predominantly female elementary teacher education program in a Philippine university. The data were gathered through online interviews and analyzed based on a phenomenological analysis framework. The following themes emerged: 1.) We hear discouraging stereotypes about teaching; 2.) We are passionate about educating the young ones; 3.) We feel that awkward moment in a room of females; and 4.) We have an inclusive learning environment. These themes are based on the individual textural and structural descriptions and form the basis for the composite textural and structural descriptions of the phenomenon of interest. This paper confirms the experiences encountered by males in the formal teaching career stage as relative to experiences received by males in the early stage of the teacher preparation. It also identifies factors that encourage males to enter elementary teacher education as a field of study, providing practical insights for designing a more inclusive program.